Synergistic combination of visible-light photo-catalytic electron and energy transfer facilitating multicomponent synthesis of β-functionalized α, α-diarylethylamines. Issue 45 (16th May 2019) - Wu, Yanan; Zhang, Yipin; Jiang, Mingjie; Dong, Xunqing; Jalani, Hitesh B.; Li, Guigen; Lu, Hongjian
Abstract : A synthetic strategy which takes advantage of the synergistic combination of electron and energy transfer processes using only one photocatalyst has been developed for the multicomponent synthesis of the α, α-diarylalkylamine skeleton. Abstract : A synthetic strategy with the visible-light photo-catalytic synergistic combination of electron and energy transfer processes has been developed. The mild reaction conditions allow the radical–radical cross-coupling phenomenon for the multicomponent synthesis of β-arylsulfonyl(diarylphosphinoyl)-α, α-diarylethyl-amines from readily available arylsulfinic acids (diarylphosphine oxides), 1, 1-diarylethylenes and arylazides.